5(4 + -1p) = 3(p + 4)
(4 * 5 + -1p * 5) = 3(p + 4)
(20 + -5p) = 3(p + 4)
Reorder the terms:
20 + -5p = 3(4 + p)
20 + -5p = (4 * 3 + p * 3)
20 + -5p = (12 + 3p)
Solving
20 + -5p = 12 + 3p
Solving for variable 'p'.
Move all terms containing p to the left, all other terms to the right.
Add '-3p' to each side of the equation.
20 + -5p + -3p = 12 + 3p + -3p
Combine like terms: -5p + -3p = -8p
20 + -8p = 12 + 3p + -3p
Combine like terms: 3p + -3p = 0
20 + -8p = 12 + 0
20 + -8p = 12
Add '-20' to each side of the equation.
20 + -20 + -8p = 12 + -20
Combine like terms: 20 + -20 = 0
0 + -8p = 12 + -20
-8p = 12 + -20
Combine like terms: 12 + -20 = -8
-8p = -8
Divide each side by '-8'.
p = 1
Simplifying
p = 1